1997
DOI: 10.1007/bf02920446
|View full text |Cite
|
Sign up to set email alerts
|

Biogas production fromJatropha curcas press-cake

Abstract: Seeds of the tropical plant Jatropha curcas (purge nut, physic nut) are used for the production of oil. Several methods for oil extraction have been developed. In all processes, about 50% of the weight of the seeds remain as a press cake containing mainly protein and carbohydrates. Investigations have shown that this residue contains toxic compounds and cannot be used as animal feed without further processing. Preliminary experiments have shown that the residue is a good substrate for biogas production. Biogas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(11 citation statements)
references
References 16 publications
0
10
1
Order By: Relevance
“…5) showed that the yields of methane were nearly equal (157.1 L·kg -1 ± 9.7 L·kg -1 VS after 10 pressure shockwaves, n = 6, α = 0.05) compared to the reference sample (149.4 L·kg -1 ± 12.3 L·kg -1 VS without any pretreatment, n = 6, α = 0.05). The methane yields achieved were low in comparison to Staubmann et al (26), which could possibly be due to the smaller size of the laboratory equipment. The key point is that the peaks of daily methane production were identical 2 days earlier in comparison to the reference samples.…”
Section: Resultscontrasting
confidence: 66%
“…5) showed that the yields of methane were nearly equal (157.1 L·kg -1 ± 9.7 L·kg -1 VS after 10 pressure shockwaves, n = 6, α = 0.05) compared to the reference sample (149.4 L·kg -1 ± 12.3 L·kg -1 VS without any pretreatment, n = 6, α = 0.05). The methane yields achieved were low in comparison to Staubmann et al (26), which could possibly be due to the smaller size of the laboratory equipment. The key point is that the peaks of daily methane production were identical 2 days earlier in comparison to the reference samples.…”
Section: Resultscontrasting
confidence: 66%
“…Nitrogen recovery is valuable, especially in developing countries with limited access to synthetic fertilizers. However application of this technology in dry climate arises two problems: high water demand and low efficiency in case of J. curcas (Chandra et al, 2012;Jabło nski et al, 2015;Staubmann et al, 1997).Plants from the Jatropha genus contain many substances regarded as antinutritional and toxic (Martínez-Herrera et al, 2006), including phytate and protease inhibitors that reduce animals' digestion rate of Jatropha seeds' biomass (Makkar et al, 1998). The concentration of these two compounds in J. curcas seeds is much higher than in oil cakes derived from other oil plants.…”
Section: Introductionmentioning
confidence: 97%
“…The oil cake remaining after the removal of oil, however, cannot be utilized as a fodder due its toxicity (Martínez-Herrera et al, 2006); production of additional energy from this substrate seems a reasonable solution. Several technologies may be used to achieve this: anaerobic digestion, alcohol fermentation, pyrolysis, and combustion (Liang et al, 2010;Ş en and Kar, 2011;Staubmann et al, 1997). The two latter methods offer high energy recovery, but anaerobic digestion enables the recovery of nitrogen from this material in the form of ammonium ions, which may be used as fertilizer (Batstone and Virdis, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…After repeated verification of the mineralization experiment, we were about to formulate concerns over whether the results reported by Achten et al. had not been overestimated; however, we later found that a mistake was made in the review: the original authors had stated that the discussed yield referred to 1 kg of degraded chemical oxygen demand.…”
Section: Resultsmentioning
confidence: 99%